he role of Donor-funded programmes on the quality of Democracy in South Africa :the case of Delft, Cape Town - Mathenjwa, Thando (My University, 2019)
After the Cold War, democracy was perceived as an ideology which had spread across the world through key mechanisms such as international development aid. In 1994 - South Africa transitioned from the Apartheid regime into a new democratic regime through domestic and international pressure. Over the past 24 years, South Africa has been a beneficiary of international development aid. Since becoming a democratic state, South Africa has continued to enjoy peaceful elections. Despite consolidating the electoral process of a democracy, this research report considered the effect donor-funded democracy programmes have on improving the quality of democracy in South Africa. This research report looked at the actors involved in the distribution of such aid and the challenges civil society face in South Africa’s democratic environment. The research showed that donor-funded programmes have the ability to boost human rights awareness and participatory culture however lack the ability to improve poor government responsiveness and accountability at a local level.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies, 2019